Community Empowerment Based on Thematic Villages in Sukorejo Sub-district, Gunungpati District, Semarang City - Sabrilla Nasya Deslita Putri; Tijan Tijan (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
This study aims to analyse the implementation of community empowerment based on thematic villages in Sukorejo Village, Gunungpati District, Semarang City. The approach used is qualitative, with data collection techniques involving in-depth interviews and field observations. The research findings indicate that community empowerment in Kampung Jawi is integrated into four main aspects: human development, business development, environmental development, and institutional development. Human development is demonstrated through the strengthening of individual capacities and the active involvement of residents in educational activities based on local culture. Business development is reflected in the development of creative economic activities such as Kampung Jawi and Pasar Jaten, which involve housewives and small and medium-sized enterprises (SMEs). Environmental development is evident in the participatory physical transformation of the village to change its negative image. Meanwhile, institutional development is realised through the strategic role of Pokdarwis and collaboration with the local government. Despite facing challenges such as low initial participation, lack of economic literacy, and reliance on central figures, the thematic village programme in Kampung Jawi has successfully fostered a more empowered, self-reliant community with a strong cultural identity. These findings indicate that the thematic village model can serve as a strategic tool in sustainable and adaptive community development rooted in local wisdom.